Dancing Fingers: Moving Mimicry and Abstract Tactility (Cinéma & Cie. Film and Media Studies Journal, 2020)
In the episode ‘Love Among the Ruins’ of Matthew Weiner’s Mad Men (AMC, S03xE02, 2009), Don Draper (John Hamm) is fascinated by Suzanne Farrell (Abigail Spencer): his fingers represent and caress the barefoot dance steps of this Flora of the sixties. I study this vicarious performance in light of the theories of empathy (Vischer, 1873) and ‘embodied simulation’ (Gallese, Freedberg, 2007). This haptic displacement of the male gaze is an erotic interplay between projection and incorporation, predatory aspirations and un-reflected imitation, the masculine and the feminine, leading to a hysterical embodiment akin to Aristotle’s tactile illusion and the reprise of scientific iconography by Max Ernst in Au Premier Mot Limpide (1923). Driven by the movement of the camera, our gaze leaves the dance and ends in foliage stirred by the wind. Watching this nonintentional ‘touch in nature’ (Ebisch, Perrucci, Ferretti, Del Gratta, Romani, Gallese, 2009), we are moved as if we mirrored a real moment of contact, both material and animistic. In discussing A Day in the Country (Une Partie de Campagne, Jean Renoir, 1936) and Jeff Wall’s A Sudden Gust of Wind (after Hokusai) (1993), I show how this visual phenomenon — an obsession of cinema — triggers an abstract and tactile empathy within us (Gallese, 2009).